Indonesia’s Cooperation with ASEAN Countries in Handling Transnational Crime Cases: South China Sea Dispute - Setyawati, Anak Agung Ayu Diah; Amandha, Asyaffa Rizdqi (Faculty of Law Universitas Negeri Semarang, 2022)
The dispute over the South China Sea is one of the disputes that has a high potential for conflict, especially in the ASEAN region. The South China Sea is a sea that irrigates many countries, such as Brunei, Malaysia, Vietnam, the Philippines China, Taiwan and Indonesia itself. Many things belong to the South China Sea, ranging from strategic interests and natural resources owned by the South China Sea. ASEAN in general and Indonesia specifically want territorial disputes in the South China Sea not to escalate into armed conflict. Therefore, Joint Development Authorities are formed in overlapping claim areas to develop the area and share the proceeds fairly without resolving the issue of sovereignty over the territory. Although not directly involved, Indonesia is neutral in disputes in the South China Sea. Indonesia has an interest in reducing the potential for such conflicts. The legal and diplomatic approach in the South China Sea conflict has been carried out by Indonesia for a long time, since the first president to the seventh president, President Jokowi and until now Indonesia is actively conducting diplomacy to realize a conducive and peaceful territorial area.